Detection and Characterization of β-Lactam Resistance in Bacillus cereus PTCC 1015 - Javad Behravan; Zeinab Rangsaaz (The Scientific World Journal)
In the present study, detection, isolation, and characterization of β-lactamases from Bacillus cereus PTCC 1015 were investigated. B. cereus was inoculated in nutrient broth containing ampicillin (50 μg.ml−1) for 24 h (35°C, 200 rpm). Activity measurements were carried out against ampicillin (0.1 mg.ml−1) and cephalexin (0.08 mg.ml−1) by a spectrophotometric method at different conditions (pH 6–10, temperatures 2545°C).Maximum penicillinase and cephalosporinase activity was observed at pH 7. The optimized temperatures for penicillinase and cephalosporinase activity were 30 and 40°C, respectively. At the above conditions, maximum enzymatic activity was calculated as 0.89 ± 0.014 and 0.037 ± 0.001 units against ampicillin and cephalexin.